Formation of the investment mechanism in the agrarian sphere of the region - Valentina Arkad'evna Li; Natal'ya Vladimirovna Vorob'yova (Экономика региона, 2011)
This paper reviews investment activity in the agrarian sector of economy of the Russian Federation during the period after overcoming the sharp phase of world financial crisis. Estimation is given to the factors constraining further improvement and development of branches of agriculture, first of all — investment activity. The question of possibility of the account of the earth as resource of mortgaging maintenance in system of crediting of agriculture is revealed. The urgency of creation of Land bank is proved; preconditions for formation of the third link of banking system are defined: a specialized financially-credit institution (mortgage, investment, ground banks with a regulation and supervision particular treatment). Measures regarding a solution of a financial maintenance problem and agriculture crediting are offered. To raise efficiency of crediting of agrarian sector, means of development of institutes of crediting of bank system taking into account post crisis factors are suggested.